The Role of the Command Center in Regulating Patient Flow in General Hospital - Luh Putu Sinthya Ulandari; Putu Aryani Astuti; Ketut Aryawati; Putu Mas Vina Paramitha Cempaka; Ni Luh Putu Nurhaeni; Tri Virgo Wati; Luh Inta Prilandari; Putu Pande Januraga (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The Command Center system has been piloted at RSUP Prof. dr. I.G.N.G. Ngoerah for approximately one year; however, its performance has not previously been evaluated. This study aimed to assess the effectiveness and efficiency of the Command Center in regulating patient flow within the hospital. A mixed methods design was employed and conducted from December 2024 to May 2025. Secondary data, consisting of referral volume reports and response time records, were analyzed descriptively. Primary data were collected through in depth interviews and focus group discussions involving seven key informants and four FGD groups, and were analyzed thematically. The findings indicate that the Command Center increased the number of accepted incoming referrals by 53%, while the proportion of unaccepted referrals decreased by 26%. The system also reduced patient congestion in the Emergency Department by enabling direct transfer of referred patients to the appropriate inpatient units based on clinical needs, bypassing the ED when necessary. Response times varied across medical staff groups, ranging from 14 to 136 minutes. However, by January 2025, approximately 93% of referrals achieved a response time of ≤60 minutes, with an average of around 20 minutes per referral. Overall, the Command Center improved the effectiveness and efficiency of the referral process, ensuring that referred patients received timely and appropriate care according to their medical condition and service requirements.Keywords: command center; effectiveness; efficiency; patient flow